The Role of Renewable Energy and Green Finance in Environmental Sustainability in East Kalimantan (Case Study: The Green Province Program of the East Kalimantan Provincial Government) - Roshada, Fariz Farhan; Ramdan, Abidea Bima; Ramdan, Darmawan; Paselle, Enos (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The issues of climate change and environmental degradation demand a transformation in development towards a more sustainable direction. One strategy adopted is the development of renewable energy and the implementation of green financing schemes, particularly at the regional level. This study aims to analyze the role of renewable energy and green financing in supporting environmental sustainability in East Kalimantan through the implementation of the Green Province Program. This research uses a qualitative descriptive approach based on literature review, with secondary data collected from various scientific sources and policy documents. The results show that although there was a decline in the Environmental Quality Index (IKLH) between 2020 and 2022, an improvement trend began to appear in 2023 and 2024 along with the increased implementation of programs such as communal solar power plants (PLTS), green microcredit, and the distribution of FCPF funds worth USD 20.9 million. The findings also highlight the importance of synergy between stakeholders and the need to scale up the revitalization of new and renewable energy infrastructure. With more thorough planning and adequate resource allocation, the Green Province Program has the potential to become a model for regionally-based low-carbon development and support the achievement of Sustainable Development Goals (SDGs) 7 and 13.